2022
DOI: 10.1177/16094069221078731
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Dilemmas in Qualitative Research: A Critical Literature Review

Abstract: The respect for ethical principles is required during the entire scientific research process, including the dissemination phase. Due to the dynamism of qualitative studies, there are often adverse ethical situations. The aim of this integrative review was to analyze and synthetize ethical dilemmas that occur during the progress of qualitative investigation and the strategies proposed to face them. The search for studies used LILACS and MEDLINE databases with descriptors “ research ethics” and “qualitative rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 59 publications
0
18
0
1
Order By: Relevance
“…The interviews were planned and applied with all the scientific, technical, and ethical guarantees usually recommended by experts (Flick, 2022;Taquette and Borges da Matta Souza, 2022). Care was taken to ensure that the interviewees understood the questions, with prior clarification of the meaning of the interview and the terms used.…”
Section: Methodsmentioning
confidence: 99%
“…The interviews were planned and applied with all the scientific, technical, and ethical guarantees usually recommended by experts (Flick, 2022;Taquette and Borges da Matta Souza, 2022). Care was taken to ensure that the interviewees understood the questions, with prior clarification of the meaning of the interview and the terms used.…”
Section: Methodsmentioning
confidence: 99%
“…The conceptual background applied to this analysis is the “ethics-as-process” framework (Cutcliffe & Ramcharan, 2002; Gibson et al, 2013; Ramcharan & Cutcliffe, 2001). Based on this framework and deriving from the emergent nature of qualitative research and hindrances to project approvals at Research Ethics Committees (RECs)(Taquette et al, 2022), ethical issues (both anticipated and evolving) should be noticed and addressed throughout the research process, rather than viewed as a one-time discrete event that is dealt with before or at the onset of the research. Doing so reflects the notion that research ethics is standardized and applied regardless of the specific context (Mattingly, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The main characteristic of this research was the challenge of understanding in depth the problem of selective garbage collection, which is typical of qualitative studies, as shown by the studies by Shelton, Philbin and Ramanadhan (2022), Taquette and Souza (2022), Harley and Cornelissen (2022) and Shaw et al (2022). It took as a unit of analysis the individuals residing in the city of Manaus, with a level of organizational analysis and perspective of synchronic analysis.…”
Section: Methodsmentioning
confidence: 99%